Development and verification of the glycolysis-associated and immune-related prognosis signature for hepatocellular carcinoma - Hu, Bo; Qu, Chao; Qi, Wei-Jun; Liu, Cheng-Hao; Xiu, Dian-Rong (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC) refers to a malignant tumor exhibiting the highest lethality. The present study aimed to identify a robust tumor glycolysis-immune-related gene signature to facilitate prognosis of HCC patients. Methods: The t-SNE algorithms were utilized to estimate the glycolysis status using the The Cancer Genome Atlas (TCGA) database-derived cohort transcriptome profiles. Moreover, prognostic genes were identified using the Cox regression model in combination with LASSO approach. The International Cancer Genome Consortium (ICGC) cohort was used for external validation. Results: Accordingly, a glycolysis-immune-related gene signature, consisting of seven genes, PSRC1, CHORDC1, KPNA2, CDCA8, G6PD, NEIL3 and EZH2, were identified among TCGA HCC patients. Under a range of conditions, the overall survival (OS) of in low-risk group patients was prolonged as compared with that of high-risk group patients. Moreover, the as-developed gene signature acted as an independent factor, significantly associated with grade, clinical stage, intrahepatic vein invasion and portal vein invasion of HCC patients. Besides, the receiver operating characteristic (ROC) curve analysis confirmed high model efficiency. Besides, the different glycolysis and immune status between the two groups were further revealed by functional analysis. Conclusions: Our as-constructed prognosis signature can be used as an approach to stratify the risk of HCC.